Is the Rate of Early mobilization in Hip fracture patients using Alfentanil Better than standard opioid analgesia (REHAB)? A protocol for a prospective cohort study - Nikhil Agarwal; Alasdair M. J. MacLullich; Nick D. Clement (Bone & Joint Open)
Aims: The primary aim of this study is to compare mobility status of patients receiving oral oxycodone with those receiving subcutaneous alfentanil as analgesic methods prior to mobilization to help physiotherapy compliance after hip fracture surgery. The secondary aims are to assess postoperative pain, health-related quality of life, in-hospital length of stay, total use of analgesia over postoperative days 1 and 2 (POD 1 and POD 2), complication rates within 30 days, and 30-day mortality rates. Methods: A single-centre, prospective cohort study of 64 patients will be undertaken. Patients undergoing surgery for femoral neck fractures at the study centre will be recruited. Patients with a hip fracture meeting the inclusion/exclusion criteria will be enrolled on admission. Patients who have been administered oral oxycodone will be compared to those prescribed alfentanil for pain prior to mobilization with physiotherapists on POD 1 and POD 2. Which drug a patient receives is reliant of the prescriptions given by the medical team, and in current practice this varies at approximately 50:50. Mobilization will be defined as the ability to stand on and weightbear both feet with or without assistance. Results: Visual analogue scale pain scores, mobility status, and total analgesia use will be assessed on POD 1 and POD 2. EuroQol five-dimension health questionnaire scores, complication rates, and mortality rates will be assessed up to 30 days following surgery (POD 1, 2, 7, and 30). Conclusion: This study will help to build a wider protocol aiming to improve early mobilization after hip fracture surgery. The results of this study will provide pain scores and mobility status which will either support use of subcutaneous alfentanil as the standard analgesic modality prior to physiotherapy sessions, or highlight its limitations compared to the standard oral oxycodone. Secondary outcomes will also help to assess if early mobilization improves outcomes compared to delayed mobilization. Cite this article: Bone Jt Open 2025;6(1):53–61.